IDENTIFICATION OF SUBSURFACE STRUCUTURE USING MAGNETOTELLURIC METHOD AT TANGKUBAN PERAHU MOUNTAIN, LEMBANG, WEST JAVA - Umbu Riada, Juldan
Tangkuban Perahu Mountain is visited by more than 1 million visitors every year. Tangkuban Perahu Mountain’s is an active mountain, which has high probability to erupt. It is important to learn about subsurface structure of Tangkuban Perahu Mountain’s area, so that structural disaster mitigation can be done in order to minimize disaster risk. One way to find out the subsurface structure is by magnetotelluric (MT) method. The MT method will produce a resistivity distribution. This resistivity distribution will be used to estimate the type of layer that is below the soil surface by inversion, which will later be interpreted with the range of rock resistivity that has been studied by geophysicists. In this report, synthetic data inversion from Mount Tangkuban Perahu will be obtained in the form of 1D and 2D models.